Construct validity using factor analysis on Malaysian street and project - Salau, Jimmy; Qistina Donna, Lee Abdullah; Salmiah, Abdul Hamid; Aliffazraie, Jali (Universiti Malaysia Terengganu, 2017)
The preservation of Malaysian Culture through the street art projects in developing the tourism industry has yet to discussed thoroughly either by the artists, researchers or academicians. Most research examines culture and heritage activities and their associations with the arts and tourism organization. Much less attention, however, has been paid to develop and validate measurement constructs of the street art projects in developing the Malaysian cultural identity. Through an extensive literature review, six dimensions of culture variables are identified. These six dimensions form the component factors of the Malaysian culture identity through the street arts project. Following a quantitative approach, a final of 53 ‐item measurement construct is validated. The factor analysis is discussed further in light of these findings.